Gestión de riesgos empresariales: marco de revisión ISO 31000 - Lizarzaburu, Edmundo R. (2017)
This research paper seeks to highlight the importance of risk management in organizations and how these should incorporate a risk management guide, following the guidelines of the ISO 31000 Guide, in order to define concepts Important such as risk culture, risk-appetite and risk-management indicators, which will enable them to better manage their organizations.